Freedom of Assembly in Poland - M. Moulin-Stożek (Теоретическая и прикладная юриспруденция)
In the chapter of the book, the author describes the procedure for normative regulation of the organization and holding of assemblies in the Republic of Poland, given that the right to freedom of assembly is enshrined in the Constitution of Poland. The author identifies certain signs and types of assemblies, depending on which a particular assembly is subject to regulation or not. In particular, the issues of holding flash mobs have not been settled. There also remain questions how to determine the boundaries when the personal moral convictions of representatives of the authorities become an obstacle to the exercise of the right to freedom of assembly, or the holding of assemblies is limited with reference to the convictions of most of the society; how to draw the line between peaceful assemblies and assemblies that threaten the safety of people; how to distinguish between spontaneous and scheduled assemblies. Some of these dilemmas are being resolved at the judicial level, but some have yet to be resolved.